Frequency of Dry Eyes with and without Posterior Blepharitis in Diabetes Patients - Faheem, Mahum; Abid, Syed; Naqvi, Hassan; Sarfaraz, Muhammad Haroon; Abidin, Farooq ul (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the frequency of dry eyes with and without posterior blepharitis in diabetic patients managed in our hospital.Study Design: Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan from Feb to Jun 2021.Methodology: A total of 160 patients suffering from type-2 Diabetes Mellitus with blood sugar fasting of more than 126mg/dl were included in the study. Dry eyes were assessed with Tear break up time tests and Schirmer. A consultant ophthalmologist conducted a detailed ophthalmological examination to diagnose posterior blepharitis among the study participants.Results: There were 160 patients enrolled in this study. The mean age was 52.68±11.8 years. The study included 74(46.3%) male and 86(53.8%) female patients. It was found that tear-breaking time was significantly lower for diabetic patients with blepharitis as compared to diabetic patients without blepharitis (p